PENGGUNAAN SPELLING DALAM PENGENALAN KOSA KATA BAHASA INGGRIS DI RUMAH PINTAR KAMPUNG KOKODA - Wael, Ahmad; A, Yuliana; Uluelang, Kris; Anggraeni, Emayanti; Din, Delika Putri (MAJU : Indonesian Journal of Community Empowerment, 2025)
Rumah Pintar Kampung Kokoda is a community empowerment facility focused on education. Rumah Pintar is located in Kokoda Village, with active Participant mostly aged 9-15 years old, equivalent to grade 3 elementary school (SD) up to grade 9 junior high school (SMP). The main focus of this service is to introduce English vocabulary using spelling, including alphabet pronunciation. The researchers involved 10 students participating from grade 3 SD to grade 9 SMP who attend learning activities at Rumah Pintar Kampung Kokoda as beneficiaries of the guidance. In response to the students' limited knowledge of spelling and vocabulary in English, the author provided a solution using picture media as a form of introducing material on spelling vocabulary in English, and also the strategy used in this activity is a play-based learning method. In this program, it is expected that the students will show significant improvement by the end of the activity; the students can more easily understand and comprehend the material provided during the activity. In this activity, students began to show more significant progress in receiving the material provided, as seen from the post-test results given. Participants on average reached level 3